2018
DOI: 10.1038/s41598-018-30790-2
|View full text |Cite
|
Sign up to set email alerts
|

A platform for discovery of functional cell-penetrating peptides for efficient multi-cargo intracellular delivery

Abstract: Cell penetrating peptides (CPPs) offer great potential to deliver therapeutic molecules to previously inaccessible intracellular targets. However, many CPPs are inefficient and often leave their attached cargo stranded in the cell’s endosome. We report a versatile platform for the isolation of peptides delivering a wide range of cargos into the cytoplasm of cells. We used this screening platform to identify multiple “Phylomer” CPPs, derived from bacterial and viral genomes. These peptides are amenable to conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 61 publications
0
41
0
Order By: Relevance
“…A reason is the slow release of the free drug to compete with its clearance. Up to now, few CPPlinked drugs have entered the clinic for both topical and systemic administration [5,306]. The first compound that entered phase II clinical trial was a cyclosporine A (CsA)-polyarginine conjugate (PsorBan1; CellGate, Inc.) for the topical treatment of psoriasis [299].…”
Section: Application Of Cpps In Clinical Trialsmentioning
confidence: 99%
“…A reason is the slow release of the free drug to compete with its clearance. Up to now, few CPPlinked drugs have entered the clinic for both topical and systemic administration [5,306]. The first compound that entered phase II clinical trial was a cyclosporine A (CsA)-polyarginine conjugate (PsorBan1; CellGate, Inc.) for the topical treatment of psoriasis [299].…”
Section: Application Of Cpps In Clinical Trialsmentioning
confidence: 99%
“…Here, in the interest of this review, we would like to mention some companies and research laboratories that have used Omomyc itself to develop their own therapeutic tools (Table 1). PYC Therapeutics (formerly Phylogica), linked Omomyc to a functional penetrating "Phylomer" peptide (FPPa) and tested the efficacy of this new entity against plasmacytoma, leukemia and breast cancer cells in vitro [86]. Similarly to what has been shown for Omomyc alone, FPPa-Omomyc blocked proliferation, induced apoptosis [85,86], disrupted MYC/MAX interaction, downregulated MYC-activated gene sets and de-repressed MYC-repressed ones.…”
Section: Ongoing Research and Future Directionsmentioning
confidence: 99%
“…PYC Therapeutics (formerly Phylogica), linked Omomyc to a functional penetrating "Phylomer" peptide (FPPa) and tested the efficacy of this new entity against plasmacytoma, leukemia and breast cancer cells in vitro [86]. Similarly to what has been shown for Omomyc alone, FPPa-Omomyc blocked proliferation, induced apoptosis [85,86], disrupted MYC/MAX interaction, downregulated MYC-activated gene sets and de-repressed MYC-repressed ones. FPPa-Omomyc showed in vivo efficacy in a subcutaneous patient-derived mouse model of triple negative breast cancer (TNBC) when administered locally, decreasing proliferation, causing apoptosis, downregulating PD-L1, and extending mouse survival [85].…”
Section: Ongoing Research and Future Directionsmentioning
confidence: 99%
“…Ample attention is also being directed to cell-penetrating peptides (CPPs), as carriers for intracellular transport cargoes such as siRNA, nucleic acids, proteins, various nano-particulate pharmaceutical carriers (e.g., liposomes, micelles), small molecule therapeutic agents as well as quantum dots and MRI contrast agents (Brasseur and Divita, 2010;Bechara and Sagan, 2013;Choi and David, 2014;Copolovici et al, 2014;Wang et al, 2014;Huang et al, 2015;Skotland et al, 2015;Dinca et al, 2016;Kurrikoff et al, 2016;Lehto et al, 2016;Guidotti et al, 2017;Hoffmann et al, 2018;Panigrahi et al, 2018;Ramaker et al, 2018;Vánová et al, 2019), since these are internalized by cells in an exceedingly effective manner. The study by Ramaker et al observed a statistically substantial dependence of CPPs' uptake efficiency on both net charge and peptide length; longer CPP possibly due to more ordered α-helical structure with high charge could ferry conjugated cargo across membranes more efficiently (Ramaker et al, 2018).…”
Section: Applications Of Peptide Self-assembliesmentioning
confidence: 99%